2017
DOI: 10.1007/s12687-017-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer genetic counseling communication with low-income Chinese immigrants

Abstract: As genetics and genomics become part of mainstream medicine, these advances have the potential to either reduce or exacerbate health disparities. Relatively, little research has explored the quality of genetic counseling communication experienced by limited English proficiency patients, especially Chinese Americans. We observed and audio recorded genetic counseling appointments (n = 40) of low-income, limited English-proficient Chinese patients (n = 25) and conducted post-visit interviews (n = 17) using stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 57 publications
(66 reference statements)
0
19
1
Order By: Relevance
“…Based upon findings of the present and related studies in which we observed uneven interpretation quality during genetic counseling (Cheng et al, 2018;Joseph et al, 2017;Kamara et al, 2018), we developed a training workshop to provide interpreters with an overview of the key concepts in genetics in general, and cancer genetics and genetic counseling specifically; it includes bilingual glossaries, vocabulary exercises and role plays (Roat et al, 2015). Furthermore, to improve interpreter and patient comprehension, we developed a training curriculum to teach GCs how they can use plain language (Stableford & Mettger, 2007), reduce the overall quantity of information they provide, and give interpreters explicit permission to ask for clarification (Joseph, Pasick, Schillinger, Guerra, & Rubin, 2018).…”
Section: Trust In the Relationship Between Interpreters And Genetic Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Based upon findings of the present and related studies in which we observed uneven interpretation quality during genetic counseling (Cheng et al, 2018;Joseph et al, 2017;Kamara et al, 2018), we developed a training workshop to provide interpreters with an overview of the key concepts in genetics in general, and cancer genetics and genetic counseling specifically; it includes bilingual glossaries, vocabulary exercises and role plays (Roat et al, 2015). Furthermore, to improve interpreter and patient comprehension, we developed a training curriculum to teach GCs how they can use plain language (Stableford & Mettger, 2007), reduce the overall quantity of information they provide, and give interpreters explicit permission to ask for clarification (Joseph, Pasick, Schillinger, Guerra, & Rubin, 2018).…”
Section: Trust In the Relationship Between Interpreters And Genetic Cmentioning
confidence: 99%
“…LHL is thought to affect about 8 million US adults (Berkman, Sheridan, Donahue, Halpern, & Crotty, 2011) and is more common among LEP individuals compared to the general population (Sentell & Braun, 2012). Genetic counseling has been shown to have a high literacy demand (Roter, 2011) and to be challenging to patients of limited literacy (Joseph et al, 2017) and LEP (Cheng et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Malen, Knerr, Delgado, Fullerton, and Thompson () found that none of the participants in their study of rural Mexican‐Americans could describe what “genetics” meant to them in their own words. In a study of low‐income Chinese immigrants, there was skepticism regarding genetic causes of cancer, with much stronger beliefs about environmental causes (Cheng et al, ). Further, acculturation among African immigrants has been found to be an important factor in the perception of genetic services (Sussner et al, ).…”
Section: Challenges and Opportunities For Genetic Counselorsmentioning
confidence: 99%
“…Researchers and healthcare practitioners have begun to explore new models of genetic counseling due to the shortage of genetic counselors, the increasing demand for their services, and the growing complexity of testing brought about by genome and exome sequencing (Bradbury et al, 2015;Hooker et al, 2014). Some have called for a shift away Our study of communication between GCs and their hereditary cancer risk counseling patients in public "safety net" hospitals assessed communication effectiveness from the patients' perspectives (Cheng et al, 2017;Joseph et al, 2017;Kamara et al, 2018;Lara-Otero et al, 2018). Through observations of 170 genetic counseling sessions with English, Spanish and Chinese-speaking patients in public hospitals and in-depth interviews with both patients and counselors, we identified a fundamental mismatch between the information provided by the GCs and the information that patients desired, deemed useful, and understood.…”
Section: Introductionmentioning
confidence: 99%